2015
DOI: 10.1186/s13012-015-0344-8
|View full text |Cite
|
Sign up to set email alerts
|

Taking hospital treatments home: a mixed methods case study looking at the barriers and success factors for home dialysis treatment and the influence of a target on uptake rates

Abstract: BackgroundDespite healthcare policies and evidence which promote home dialysis, uptake rates have been falling for over 10 years in England. A target introduced by commissioners in the West Midlands provided a unique opportunity to study how hospitals can increase home-based treatment for a group of patients with complex life-threatening conditions.MethodsQuantitative changes in home treatment uptake rates in seven hospitals in the West Midlands were compared with the rest of England for 3 years pre and post t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 22 publications
0
31
0
1
Order By: Relevance
“…Between 2010 and 2012, the West Midlands introduced a commissioning target to increase HT uptake, with evidence that this led to an increase in HT rates [3]. This can also be seen in the UKRR data.…”
Section: Centre-level Home Therapy Use and Changes Over Timementioning
confidence: 50%
“…Between 2010 and 2012, the West Midlands introduced a commissioning target to increase HT uptake, with evidence that this led to an increase in HT rates [3]. This can also be seen in the UKRR data.…”
Section: Centre-level Home Therapy Use and Changes Over Timementioning
confidence: 50%
“…A recent study reported that more than a third of people who are new to dialysis had experienced emotional and psychological difficulties, yet there was an absence of support for patients whose psychosocial problems fell below the threshold of clinical depression (Combes et al . ). Although patients who have ESKD want improved support, particularly in the areas of coping and adjustment, their needs tend to be ignored and frequently remain untreated (Schell et al .…”
Section: Introductionmentioning
confidence: 97%
“…depression (Combes et al 2015). Although patients who have ESKD want improved support, particularly in the areas of coping and adjustment, their needs tend to be ignored and frequently remain untreated (Schell et al 2012;Gill & Lowes 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dialysis and renal transplantation are life-saving treatments, but they are also demanding and impact appreciably on the everyday lives of end-stage renal disease (ESRD) patients, often negatively affecting emotional and psychological well-being. Many patients find the transition to dialysis frightening and traumatic [ 1 3 ]. They can continue to experience periods of distress throughout their time on dialysis due to the stress of treatment, loss of sexual function, altered body image and decreased physical and cognitive functioning, as well as consequent effects on employment, relationships and lifestyle [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…No robust data exist on the prevalence of lower-level emotional and psychological problems, defined as difficulties in coping effectively with the diagnosis, physical symptoms and treatment, which result in distress, poor emotional adjustment and reduced quality of life [ 12 , 13 ]. Nonetheless, a recent study found that more than a third of dialysis patients experienced emotional difficulties, particularly during the transition to dialysis and early months on dialysis [ 3 ]. Furthermore, untreated psychosocial problems are associated with withdrawal from dialysis [ 14 , 15 ], poor medication and diet compliance [ 16 18 ] and reduced ability to engage in pre-renal replacement therapy education and treatment choice [ 3 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%